Antioxidant activity and determination of bioactive compounds by GC-MS in fruit methanol extracts -a comparative analysis of three Atalantia species from south India - Arun K Das, Sudhakar Swamy (Journal of Applied Pharmaceutical Science, 2016)
The members of genus Atalantia are widely used in Traditional, Folk and Ayurvedic systems of Medicine; of which three species are found in south India namely A. monophylla, A. racemosa, A. wightii. The fruits of these plants are picked and widely consumed by the tribal people. The present study aims to test the anti-oxidant potential of the methanol extracts of fruits and also to identify the bioactive compounds present in the extracts through GC/MS analysis. Among the three fruits tested for the antioxidant activity using the DPPH method, the crude methanolic extracts of A. monophylla shows higher potential. The IC50 value calculated was found to be 336.84 μg/ml for A. monophylla, 348.75 μg/ml for A. racemosa and 375.64 μg/ml for A. wightii. Ascorbic acid used as standard had an IC50 value of 103.03 μg/ml. Total antioxidant capacity was expressed as ascorbic acid equivalent and was calculated using the Phosphomolybdenum method. The methanol extract of A. monophylla, A. racemosa and A. wightii determined by phosphomolybdenum method exhibited significant antioxidant activity of 686mg/g, 592 mg/g and 655mg/g ascorbic acid equivalent respectively. Also the bioactive compounds in the Methanol extracts were evaluated using GC/MS.
Keywords: Atalantia, GC/MS, Antioxidant activity, Bioactive compounds.